Mary Elizabeth Hallock Greenewalt papers - Greenewalt, Mary Elizabeth Hallock, 1871-1950.; Greenewalt, Mary Elizabeth Hallock, 1871-1950.
Correspondence, speeches, writings, legal and financial records, biographical material, printed matter, and annotated photographs relating chiefly to Greenewalt's invention of an art form called Nourathar (also Sarabet, Light-Score), which harmonized projected patterns of colored light with concert music. Includes drafts of her book titled Nourathar, the fine art of light color playing, published in 1946. Correspondents include Howson & Howson and Busser & Harding, Greenewalt's attorneys in Philadelphia, Pa., as well as various government agencies.
Musician, inventor, and author.
Collection material in English.
Finding aid available in the Library of Congress Manuscript Reading Room and at
Keywords: Busser & Harding -- Correspondence; Howson & Howson -- Correspondence; Music; Music and color; Authors; Inventors; Musicians